2015
DOI: 10.3171/2014.10.jns132694
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of premorbid hypertension and neurological status in aneurysmal subarachnoid hemorrhage: pooled analyses of individual patient data in the SAHIT repository

Abstract: obJect The literature has conflicting reports about the prognostic value of premorbid hypertension and neurological status in aneurysmal subarachnoid hemorrhage (SAH). The aim of this study was to investigate the prognostic value of premorbid hypertension and neurological status in the SAH International Trialists repository. methods Patient-level meta-analyses were conducted to investigate univariate associations between premorbid hypertension (6 studies; n = 7249), admission neurological status measured on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 45 publications
3
16
1
Order By: Relevance
“… 17 23 29 30 A recent study reported that premorbid hypertension is an independent risk factor for a 3-month functional outcome of aSAH. 31 However, in this study, the prognostic power appeared weak and the definition of premorbid hypertension was ambiguous. In addition, whether the patients with hypertension were appropriately controlled with hypertensive medication was unclear.…”
Section: Discussionmentioning
confidence: 62%
“… 17 23 29 30 A recent study reported that premorbid hypertension is an independent risk factor for a 3-month functional outcome of aSAH. 31 However, in this study, the prognostic power appeared weak and the definition of premorbid hypertension was ambiguous. In addition, whether the patients with hypertension were appropriately controlled with hypertensive medication was unclear.…”
Section: Discussionmentioning
confidence: 62%
“…Independent covariates included in this analysis were previously identified predictors of outcome from previous analyses based on the CONSCIOUS-1 study 20,21 and those previously identified as independent prognostic factors for poor outcome after aSAH. 22 These included age, preexisting hypertension, poor WFNS scores on admission (dichotomized as WFNS IV-V versus I-III), subarachnoid clot burden, aneurysm location (posterior versus anterior), aneurysm size (<5 mm versus >5 mm), and angiographic vasospasm (none/mild versus moderate/severe).…”
Section: Discussionmentioning
confidence: 99%
“… 1 3 Despite studies demonstrating the safety of early obliteration, 4 6 the rate of rebleeding is still high. 3 , 6 , 7 Most studies reveal that rebleeding often occurs within 3 days of the presenting hemorrhage. 5 , 7 9 Therefore, it will be beneficial to identify a subgroup of patients with high risk of rebleeding in the acute phase of subarachnoid hemorrhage (SAH).…”
Section: Introductionmentioning
confidence: 99%